The Effect of Logic Therapy Combined with Quran Recitation and Prayer on Depression Symptoms in Women with Major Depressive Disorder - Nafiseh Rafiei Mohammadi; Mohammad Mehdi Jahangiri (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Major Depressive disorders are one of the most common and chronic disorders that require treatment. The present study was an attempt to investigate the effect of Logotherapy with Quran recitation and prayer on severity of depressive symptoms in women with major depressive disorder. Methods: This study used a quasi-experimental pretest-posttest control group design. The statistical population included all women with depressive disorder in Qom in 2017. The sample population consisted of 30 women with major depressive disorder (15 for each group) and the participants were selected on a voluntary basis. They were randomly assigned to experimental and control groups. The instrument used for gathering data was Beck depression Inventory. The data were analyzed using ANCOVA. In the present study, all ethical considerations were observed and the authors reported no conflict of interest. Results: In terms of severity of depressive symptoms, the mean scores for the experimental and control groups at the pretest stage were 35.80 and 33.60, respectively. Meanwhile, the mean scores were 19.86 for the experimental group and 32.46 for the control group. The level of depression remained unchanged in the control group but decreased in the experimental group at the post-test phase following the intervention, which was statistically significant (P<0.001). Conclusion: The findings indicate that Logotherapy along with Quran recitation and prayer is effective in reduction of the symptoms of depression in women with major depression.For downloading the full-text of this article please click here. Please cite this article as: Rafiei Mohammadi N, Jahangiri MM. The Effect of Logic Therapy Combined with Quran Recitation and Prayer on Depression Symptoms in Women with Major Depressive Disorder. Pizhūhish dar dīn va salāmat. 2020; 5(4):88-98. https://doi.org/10.22037/jrrh.v5i4.21692